A high-density anti-cracking nano-modified pyrophyllite composite pressure transmission medium and a preparation method thereof

CN122999061APending Publication Date: 2026-10-30ZHEJIANG HAOXIANG MINING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611464896.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统叶蜡石传压块在实际应用中普遍存在以下问题:(1)单面压制或普通双面压制工艺导致生坯上下表面密度差大,高温高压下各向传压不均,影响合成腔体内压力场的均匀性,进而降低金刚石单产和品级

Benefits of technology

[0042]在本发明中,通过特定三级粒度物理级配、纳米改性材料表面包覆、双面顶压成型及五段式程序控温干燥的组合,共同提高成型体的致密性和抗开裂性能,具体而言:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999061A_ABST
    Figure CN122999061A_ABST
Patent Text Reader

Abstract

The application provides a high-density anti-cracking nano-modified pyrophyllite composite sealing pressure transmission medium and a preparation method thereof. The preparation raw materials include the following components in parts by weight: 88-94 parts of natural pyrophyllite, 2-6 parts of nano-modified material and 4-8 parts of water glass binder, and the total weight of the components is 100 parts; the preparation method comprises the following steps: crushing and screening the natural pyrophyllite ore, uniformly mixing the obtained coarse, medium and fine pyrophyllite particles in a mass ratio of (2-3) : 3 : (4-5); adding the nano-modified material into anhydrous ethanol and a dispersant, obtaining a nano-suspension through ultrasonic treatment and spraying the nano-suspension onto the surface of the graded pyrophyllite particles, then adding the water glass binder for granulation, and finally drying the product through five-stage programming to obtain the high-density anti-cracking nano-modified pyrophyllite composite sealing pressure transmission medium. The finished product is in the form of a hollow cube, the density is greater than or equal to 2.65 g / cm 3 , the density difference between the upper and lower surfaces is less than or equal to 0.04 g / cm 3 , the cracking rate at 800 DEG C is 0%, and the sealing leakage volume flow is less than or equal to 0.13 mL / min, thereby effectively solving the problems of uneven density, easy cracking and poor sealing performance of the existing pyrophyllite pressure transmission medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of auxiliary materials for superhard materials used in the synthesis of synthetic diamonds, specifically relating to a high-density, crack-resistant, nano-modified pyrophyllite composite sealing pressure transmission medium for the synthesis of synthetic diamonds under high temperature and high pressure (HPHT) and its preparation method. Background Technology

[0002] Synthetic diamonds are usually synthesized using the high temperature and high pressure (HPHT) method. Pyrophyllite, due to its good pressure transmission, sealing, insulation and heat preservation properties, is often made into pyrophyllite blocks or composite pressure transmission media to form the synthesis cavity of synthetic diamonds. However, the following problems are common in the practical application of traditional pyrophyllite pressure transmission blocks: (1) Single-sided pressing or ordinary double-sided pressing process leads to a large density difference between the upper and lower surfaces of the green blank, and uneven pressure transmission in all directions under high temperature and high pressure, which affects the uniformity of the pressure field in the synthesis cavity, thereby reducing the diamond yield and grade. (2) Pyrophyllite is prone to phase transformation and dehydration at high temperature. If there is too much residual moisture or unreasonable particle size distribution, microcracks or even explosions (blasting) will occur, causing synthesis failure and safety accidents. (3) The sealing performance of traditional pyrophyllite blocks decreases with increasing temperature, making it difficult to meet the requirements of long-term high temperature and high pressure synthesis.

[0003] To address the aforementioned issues, existing technologies typically improve upon them in the following ways: first, by adding inorganic modifiers and binders to adjust the composition and structure of the pressure-transmitting medium; second, by optimizing particle size distribution (e.g., using multi-stage particle size mixing) to improve bulk density and filling uniformity; third, by improving molding processes (e.g., isostatic pressing, biaxial pressing) to reduce the density difference of the green body; and fourth, by adjusting heat treatment or drying regimes to control moisture release and phase change behavior. However, existing improvement methods are limited to optimizing a single stage or single parameter, failing to achieve a synergistic design across the entire process. Therefore, existing pyrophyllite pressure-transmitting media still face the following shortcomings under high temperature and high pressure conditions: uneven dispersion of modified components in the matrix leads to local performance fluctuations; a large density difference between the upper and lower surfaces of the green body causes pressure transmission anisotropy; and excessively rapid moisture release or high residual moisture during drying can easily induce microcracks or even bursts, making it difficult to simultaneously improve the sealing stability, pressure transmission uniformity, and crack resistance of synthetic diamond products, thus hindering their further development.

[0004] In view of this, the present invention is hereby proposed. Summary of the Invention

[0005] This invention aims to provide a high-density, crack-resistant, nano-modified pyrophyllite composite sealing and pressure-transmitting medium and its preparation method. A combination of specific three-level particle size distribution, surface coating with nano-modified materials, double-sided top-pressure molding, and five-stage programmed temperature-controlled drying collectively improves the density and crack resistance of the molded material.

[0006] To achieve the above objectives, the present invention provides a method for preparing a high-density, crack-resistant, nano-modified pyrophyllite composite sealing pressure transmission medium. The raw materials for preparing the pressure transmission medium include the following components by weight: 88-94 parts of natural pyrophyllite, 2-6 parts of nano-modified material, and 4-8 parts of water glass binder, and the total weight of each component is 100 parts.

[0007] The nano-modified material is at least one of nano-talc, nano-diatomite, nano-rutile, and nano-hematite;

[0008] The specific preparation method includes the following steps:

[0009] (1) Crush, grind and screen the natural pyrophyllite ore to separate coarse particles with a particle size of 1 mm to 2.36 mm, medium particles with a particle size of 0.5 mm to 1 mm and fine particles with a particle size of 0.1 mm to 0.5 mm. Weigh the pyrophyllite particles in each particle size range according to the mass ratio of coarse, medium and fine particles of (2 to 3): 3: (4 to 5) and mix them evenly.

[0010] (2) The nano-modified material is dispersed in anhydrous ethanol, and a dispersant is added for ultrasonic dispersion to form a stable nano suspension;

[0011] (3) The suspension obtained in step (2) is applied to the surface of the pyrophyllite particles in a rolling state by atomized spraying, mixed evenly and evaporated to dry, to obtain the graded powder with surface coating.

[0012] (4) Add water glass binder to the graded powder obtained in step (3), stir evenly, and obtain a mixture;

[0013] (5) Place the mixture obtained in step (4) into a mold and press it into shape using a double-sided pressing process to obtain a green block;

[0014] (6) Place the green block obtained in step (5) into a programmable temperature-controlled oven for five-stage stepped heating and drying, and obtain the finished product after cooling.

[0015] In a preferred embodiment, the particle size D of the nanotalc is... 50 The particle size D of nano-diatomite ranges from 50 nm to 200 nm. 50 The particle size D of nano-rutile is 30 nm to 150 nm. 50 The particle size D of nano-hematite ranges from 40 nm to 120 nm. 50 The wavelength range is 40 nm to 120 nm.

[0016] In a preferred embodiment, in step (1), the mass ratio of the coarse particles, medium particles and fine particles is 2:3:5 or 3:3:4.

[0017] This invention designs a specific three-level particle size distribution, so that fine particles fill the gaps between medium particles and medium particles fill the gaps between coarse particles, thereby obtaining the minimum porosity and the maximum initial packing density, which is more conducive to the subsequent nano-coating of pyrophyllite.

[0018] In a preferred embodiment, in step (2), the mass ratio of the nano-modified material to anhydrous ethanol is 1:(5.7~19.5).

[0019] In a preferred embodiment, in step (2), the dispersant is polyethylene glycol 400 or polyvinylpyrrolidone K30, and the amount of the dispersant added is 0.5% to 3% of the weight of the nano-modified material.

[0020] In a preferred embodiment, in step (2), the power density of the ultrasonic dispersion is 50 W / L to 100 W / L, and the time is 20 min to 60 min.

[0021] In a preferred embodiment, in step (2), the solid content of the nano suspension is 5 wt%~15 wt%, and the absolute value of the Zeta potential is ≥35 mV.

[0022] In a preferred embodiment, in step (3), the nozzle orifice diameter of the atomizing spray is 0.5 mm to 1.5 mm, the spray pressure is 0.2 MPa to 0.5 MPa, and the spray flow rate is 50 mL / min to 200 mL / min.

[0023] In this invention, the solid content, Zeta potential, and spraying parameters (nozzle aperture, pressure, and flow rate) of the nano-suspension were specifically designed to ensure that the nanoparticles are monodisperse in the suspension and uniformly deposited as atomized droplets on the surface of the tumbling pyrophyllite particles. If the solid content is too low, the coating layer will be too thin and unable to form a continuous film; if the solid content is too high, the viscosity of the suspension will increase and the atomization effect will deteriorate. Furthermore, experiments showed that when the Zeta potential is below 35 mV, the nanoparticles will agglomerate during spraying and drying, disrupting the uniformity of the coating layer.

[0024] In a preferred embodiment, in step (3), after the spraying is completed, the process further includes continuing to tumble for 10 min to 30 min before evaporation and drying.

[0025] In a preferred embodiment, step (3) specifically includes the following operations: evaporating and drying at 60°C to 90°C until the residual ethanol content is ≤0.5 wt%.

[0026] In a preferred embodiment, in step (3), the D of the surface-coated graded powder50 Its thickness ranges from 0.3 mm to 1.5 mm, and its specific surface area is 10 m². 2 / g~30 m 2 / g.

[0027] In a preferred embodiment, in step (4), the modulus of the water glass adhesive is 2.0 to 3.5 and the Baume degree is 30°Bé to 50°Bé.

[0028] In a preferred embodiment, in step (4), the water glass adhesive is added by spraying, and stirring is continued for 5 min to 15 min after addition.

[0029] In a preferred embodiment, in step (5), the pressing pressure of the double-sided top pressing process is 250 MPa to 300 MPa, and the holding time is 10 s to 30 s.

[0030] This invention employs simultaneous pressure from upper and lower punches, symmetrically transmitting pressure from both sides towards the center, achieving equilibrium at the neutral plane, thereby ensuring a uniform density distribution throughout the thickness direction. Furthermore, the pressing pressure is adaptively designed to accommodate the pyrophyllite particle gradation and the mechanical properties of the coating layer. Insufficient pressure is inadequate for sufficient particle rearrangement and plastic deformation; excessive pressure may damage the nano-coating layer or cause the pyrophyllite particles themselves to break.

[0031] In a preferred embodiment, in step (5), the pressed green block is a hollow cube with an outer contour size of 53 mm × 53 mm × 53 mm and a wall thickness of 8 mm to 12 mm.

[0032] In a preferred embodiment, in step (6), the temperature, holding time, and heating rate of each stage of the five-stage program drying satisfy the following conditions:

[0033] First stage: Increase the temperature to 95℃~105℃ at a rate of 1.0℃ / min~2.0℃ / min, and hold for 6 h~10 h;

[0034] Second stage: Increase the temperature to 115℃~135℃ at a rate of 0.5℃ / min~1.5℃ / min, and hold for 4 h~6 h;

[0035] The third stage: the temperature is increased to 175℃~185℃ at a rate of 0.5℃ / min~1.0℃ / min, and held for 3 h~4 h;

[0036] Fourth stage: Increase the temperature to 225℃~235℃ at a rate of 0.3℃ / min~0.8℃ / min, and hold for 3 h~4 h;

[0037] Fifth stage: Increase the temperature to 275℃~285℃ at a rate of 0.3℃ / min~0.5℃ / min, and hold for 3 h~5 h.

[0038] In the five-stage temperature-controlled drying process of this invention, the first stage removes free water and residual ethanol. This water exists in liquid form in the interparticle spaces and evaporates rapidly, requiring a longer holding time to prevent rapid surface drying and crust formation. The second stage removes capillary water, which exists in micropores and requires higher temperatures to drive diffusion. In the third stage, the water glass begins initial dehydration and condensation, releasing structural water. The heating rate needs to be slowed down to avoid a sudden increase in water vapor pressure. In the fourth stage, the water glass further crosslinks and solidifies, while the nano-modified material begins partial dehydration. The fifth stage completes the final dehydration reaction.

[0039] In a preferred embodiment, in step (6), the bulk density of the pressure-transmitting medium is 2.65 g / cm³. 3 The density difference between its upper and lower surfaces is 0.04 g / cm³. 3 The following products, after high-temperature sintering, exhibit no cracking and have a leakage volumetric flow rate below 0.13 mL / min.

[0040] Another object of the present invention is to provide a nano-modified pyrophyllite composite sealing pressure transmission medium prepared by any of the above methods.

[0041] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0042] In this invention, the density and crack resistance of the molded body are improved by combining specific three-level particle size physical gradation, surface coating with nano-modified materials, double-sided top-press molding, and five-stage programmed temperature-controlled drying. Specifically:

[0043] The three-level particle size distribution follows the theory of close packing, which allows coarse, medium and fine particles to fill each other in a specific ratio, minimizing porosity and increasing initial packing density, thus providing a dense particle skeleton for subsequent pressing.

[0044] The surface coating of nano-modified materials forms a continuous and uniform core-shell structure on the surface of pyrophyllite particles through ultrasonic dispersion and atomized spraying. On the one hand, the layered lubrication effect of nano-talc relieves stress concentration and inhibits the initiation of microcracks. On the other hand, it enables nano-diatomite and rutile to be precisely positioned at the particle interface, generating a ceramic bonding phase in situ at high temperature and reducing thermal conductivity, thereby simultaneously achieving the dual effects of interface strengthening and thermal regulation.

[0045] Double-sided top-pressing eliminates the inherent pressure gradient of single-sided pressing by applying pressure simultaneously from the upper and lower punches, making the density distribution of the green blank along the thickness direction more uniform, and ensuring that the overall density and density uniformity meet the standards simultaneously.

[0046] The five-stage programmed temperature-controlled drying precisely matches the form of moisture and the escape dynamics of each temperature range, allowing free water, capillary water, and bound water to be discharged slowly in stages. This not only thoroughly removes residual moisture to prevent high-temperature explosions but also avoids internal stress cracking caused by rapid surface drying and crusting, ultimately ensuring the structural integrity and reliability of the finished product under high-temperature and high-pressure conditions.

[0047] Through the synergistic effect of the above technical means, this invention solves the long-standing technical problems in the field of pressure transmission media, such as the difficulty in balancing high density and low density differences, easy cracking, and explosion, and provides a high-performance, stable, safe and reliable pressure transmission sealing solution for the high-temperature and high-pressure synthesis of synthetic diamond. Attached Figure Description

[0048] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0049] Figure 1 This is a physical image of the nano-modified pyrophyllite composite sealing pressure transmission medium prepared in Example 1 of the present invention.

[0050] Figure 2 This is a physical image of the pressure-transmitting medium prepared in Comparative Example 1 of the present invention. Detailed Implementation

[0051] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0052] Unless otherwise specified, the technical means used in this invention are conventional means well known to those skilled in the art. All raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared using existing methods. Unless otherwise specified, all reagents used in this invention are of analytical grade.

[0053] The natural pyrophyllite ore used in this embodiment of the invention was mined from Qingtian County, Zhejiang Province, and its main chemical composition is shown in Table 1:

[0054] Table 1. Analysis results of the main elemental chemical composition of pyrophyllite (wt%)

[0055] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> CaO 67.74 31.19 0.29 0.15 0.17 0.07

[0056] The nano-modified materials used in the embodiments of this invention were all purchased from a mineral products company in Henan Province. The average particle size D of the nano-talc was... 50 The average particle size of the nano-diatomite is 120 nm, with a purity of 99.0%; D0 50 It has a wavelength of 85 nm, a purity of 99.5%, and a specific surface area of ​​102.6 m². 2 / g; Average particle size D of nano rutile 50 The average particle size of nano-hematite is 80 nm; 50 It has a wavelength of 80 nm, a purity of 99.5%, and a specific surface area of ​​88.1 m². 2 / g.

[0057] The water glass binder used in this embodiment of the invention was purchased from Beijing Jintongletai Chemical Products Co., Ltd., with a modulus of 3.27, a Baume degree of 40°Bé, and a solid content of 36.75 wt%; the dispersant used was polyethylene glycol 400 (PEG-400), which was chemically pure.

[0058] In this invention, the weight parts can be weight units known in the art such as µg, mg, g, kg, or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.

[0059] The detection method involved in the embodiments of the present invention includes:

[0060] (1) The Zeta potential was measured using a Malvern Zetasizer Nano ZS potential analyzer at a test temperature of 25℃.

[0061] (2) Density: The density was determined by using a Mettler Toledo MS204TS electronic balance with a density component. After the sample was treated with wax impregnation and sealing, the density was determined by Archimedes' water displacement method. The test temperature was 25℃ and deionized water was used as the impregnation solution.

[0062] (3) Density difference: The green or finished product is evenly cut into three layers along the thickness direction: upper, middle and lower. The density of each layer is measured and the absolute value of the difference between the density of the upper surface layer and the lower surface layer is taken.

[0063] (4) Cracking rate: The finished product is placed in a muffle furnace and heated to 800°C at a heating rate of 10°C / min. After holding at the temperature for 30 minutes, it is naturally cooled to room temperature. The sample surface is observed under a 20x magnifying glass. The percentage of samples with visible cracks is counted. 20 samples are tested in each group.

[0064] (5) Leakage volume flow rate: The finished hollow cube sample was cleaned and dried. Helium was filled to 0.5MPa using the helium hood method according to GB / T15823. The leakage volume flow rate was tested using a helium mass spectrometer. 20 samples were tested in each group.

[0065] Example 1

[0066] S1. Take natural pyrophyllite ore, crush it to a particle size of less than 5mm using a jaw crusher, and then grind it for 20 minutes using a star ball mill. The grinding media is zirconia balls, the ball-to-material ratio is 3:1, and the rotation speed is 300rpm. All the ground material passes through a 2.36mm standard inspection sieve.

[0067] The ground pyrophyllite powder was sequentially passed through standard inspection sieves of 2.36 mm, 1 mm, 0.5 mm, and 0.1 mm for 10 minutes with a vibration amplitude of 2 mm. Materials from three particle size ranges were collected: coarse particles (1 mm to 2.36 mm), medium particles (0.5 mm to 1 mm), and fine particles (0.1 mm to 0.5 mm).

[0068] S2. Weigh out 4 g of nano-talc, 3 g of nano-boehmite, 2 g of nano-rutile, and 1 g of nano-hematite and mix them as the nano-modified material. Disperse 10 g of the nano-modified material in 0.10 L of anhydrous ethanol, then add 0.15 g of dispersant and perform ultrasonic dispersion. The power density of ultrasonic dispersion is 80 W / L, and the time is 40 min. Immediately after dispersion, take a sample and measure the Zeta potential. The result is -46.8 mV, and the absolute value is greater than 35 mV, indicating that the suspension is stable.

[0069] S3. Weigh 225 g of three-graded pyrophyllite particles, including 45 g of coarse particles, 67.5 g of medium particles, and 112.5 g of fine particles (coarse, medium, and fine particle mass ratio = 2:3:5). Add the particles to a mixer, set the speed to 15 rpm, and start the tumbling process. Transfer the nano-suspension prepared in step S2 to a storage tank and spray it through an atomizing spray system. The nozzle orifice diameter is 0.8 mm, the spray pressure is 0.3 MPa, and the spraying time is approximately 3 minutes. During the spraying process, keep the pyrophyllite particles continuously tumbling. After spraying, continue tumbling for 15 minutes to allow the liquid film to fully spread. Then transfer the material to a dryer and dry it at 80℃ until the residual ethanol content is ≤0.5 wt%, obtaining a surface-coated graded powder. Observation of the microstructure of the obtained powder shows that the nano-modified material forms a continuous and uniform coating layer on the surface of the pyrophyllite particles. No obvious large-sized agglomerates are observed on the particle surface. Particle size analysis shows D... 50 The thickness is 0.86 mm, and the specific surface area of ​​BET is 18.6 m². 2 / g.

[0070] S4. Add 15 g of water glass binder (modulus 3.27, Baume degree 40°Bé) to the obtained graded powder by spraying evenly at a pressure of 0.2 MPa for 1 minute. Maintain the mixer speed at 20 rpm during the addition process. After the addition is complete, continue stirring for 10 minutes to obtain the mixture.

[0071] S5. Fill the mixture into a hollow cubic mold. The mold's outer cavity dimensions are 53mm × 53mm × 53mm, the mandrel dimensions are 37mm × 37mm × 37mm, and the wall thickness is 8mm. The mold material is Cr12MoV mold steel. A double-sided hydraulic press is used for pressing, with the upper and lower punches applying pressure simultaneously. The pressure is set to 280MPa, and the holding time is 20s. During pressing, the displacement of the upper and lower punches is monitored in real time, and the stroke deviation is controlled within 0.3mm. After demolding, a green cube is obtained.

[0072] S6. Place the green block into a programmable temperature-controlled oven and dry it using the following parameters in a five-stage program:

[0073] First stage: Heat to 100℃ at a rate of 1.5℃ / min, and hold at 100℃±2℃ for 8 hours;

[0074] Second stage: Increase the temperature to 130℃ at a rate of 1.0℃ / min, and hold at 130℃±2℃ for 5 hours;

[0075] The third stage: the temperature is increased to 180℃ at a rate of 0.8℃ / min, and then held at 180℃±2℃ for 3.5 hours;

[0076] Fourth stage: Increase the temperature to 230℃ at a rate of 0.5℃ / min, and hold at 230℃±2℃ for 3.5 hours;

[0077] Fifth stage: Increase the temperature to 280℃ at a rate of 0.4℃ / min, and hold at 280℃±2℃ for 4 hours.

[0078] After drying, turn off the oven power and allow the sample to cool naturally to room temperature (approximately 25°C) to obtain the finished product. The density of the finished product is measured: the overall density is 2.68 g / cm³. 3 The density difference between the upper and lower surfaces is 0.02 g / cm³. 3 .

[0079] Example 2

[0080] S1. Take natural pyrophyllite ore, crush it to a particle size of less than 5mm using a jaw crusher, and then grind it for 20 minutes using a star ball mill. The grinding media is zirconia balls, the ball-to-material ratio is 3:1, and the rotation speed is 300rpm. All the ground material passes through a 2.36mm standard inspection sieve.

[0081] The ground pyrophyllite powder was sequentially passed through standard inspection sieves of 2.36 mm, 1 mm, 0.5 mm, and 0.1 mm for 10 minutes with a vibration amplitude of 2 mm. Materials from three particle size ranges were collected: coarse particles (1 mm to 2.36 mm), medium particles (0.5 mm to 1 mm), and fine particles (0.1 mm to 0.5 mm).

[0082] S2. Weigh 4 g of nano-talc and 6 g of nano-boehmite as the nano-modified materials. Disperse 10 g of the nano-modified materials in 0.10 L of anhydrous ethanol, then add 0.15 g of dispersant and perform ultrasonic dispersion. The ultrasonic dispersion power density is 80 W / L and the time is 40 min. Immediately after dispersion, take a sample to measure the Zeta potential. The result is -44.2 mV, and the absolute value is greater than 35 mV, indicating that the suspension is stable.

[0083] S3. Weigh 225 g of three-graded pyrophyllite particles, including 67.5 g of coarse particles, 67.5 g of medium particles, and 90 g of fine particles (coarse, medium, and fine particle mass ratio = 3:3:4). Add the particles to a mixer, set the speed to 15 rpm, and start the tumbling process. Transfer the nano-suspension prepared in step S2 to a storage tank and spray it through an atomizing spray system. The nozzle orifice diameter is 0.8 mm, the spray pressure is 0.3 MPa, and the spraying time is approximately 3 minutes. During the spraying process, keep the pyrophyllite particles continuously tumbling. After spraying, continue tumbling for 15 minutes to ensure the liquid film is fully spread. Then transfer the material to a dryer and dry it at 80℃ until the residual ethanol content is ≤0.5 wt%, obtaining a surface-coated graded powder. The resulting powder D... 50 The thickness is 0.77 mm, and the specific surface area of ​​BET is 17.2 m². 2 / g.

[0084] S4. Add 15 g of water glass binder (modulus 3.27, Baume degree 40°Bé) to the obtained graded powder by spraying evenly at a pressure of 0.2 MPa for 1 minute. Maintain the mixer speed at 20 rpm during the addition process. After the addition is complete, continue stirring for 10 minutes to obtain the mixture.

[0085] S5. Fill the mixture into a hollow cubic mold. The mold's outer cavity dimensions are 53mm × 53mm × 53mm, the mandrel dimensions are 37mm × 37mm × 37mm, and the wall thickness is 8mm. The mold material is Cr12MoV mold steel. A double-sided hydraulic press is used for pressing, with the upper and lower punches applying pressure simultaneously. The pressure is set to 280MPa, and the holding time is 20s. During pressing, the displacement of the upper and lower punches is monitored in real time, and the stroke deviation is controlled within 0.3mm. After demolding, a green cube is obtained.

[0086] S6. Place the green block into a programmable temperature-controlled oven and dry it using the following parameters in a five-stage program:

[0087] First stage: Heat to 100℃ at a rate of 1.5℃ / min, and hold at 100℃±2℃ for 8 hours;

[0088] Second stage: Increase the temperature to 130℃ at a rate of 1.0℃ / min, and hold at 130℃±2℃ for 5 hours;

[0089] The third stage: the temperature is increased to 180℃ at a rate of 0.8℃ / min, and then held at 180℃±2℃ for 3.5 hours;

[0090] Fourth stage: Increase the temperature to 230℃ at a rate of 0.5℃ / min, and hold at 230℃±2℃ for 3.5 hours;

[0091] Fifth stage: Increase the temperature to 280℃ at a rate of 0.4℃ / min, and hold at 280℃±2℃ for 4 hours.

[0092] After drying, turn off the oven power and allow the sample to cool naturally to room temperature (approximately 25°C) to obtain the finished product. The density of the finished product is measured: the overall density is 2.66 g / cm³. 3 The density difference between the upper and lower surfaces is 0.03 g / cm³. 3 .

[0093] Example 3

[0094] S1. Take natural pyrophyllite ore, crush it to a particle size of less than 5mm using a jaw crusher, and then grind it for 20 minutes using a star ball mill. The grinding media is zirconia balls, the ball-to-material ratio is 3:1, and the rotation speed is 300rpm. All the ground material passes through a 2.36mm standard inspection sieve.

[0095] The ground pyrophyllite powder was sequentially passed through standard inspection sieves of 2.36 mm, 1 mm, 0.5 mm, and 0.1 mm for 10 minutes with a vibration amplitude of 2 mm. Materials from three particle size ranges were collected: coarse particles (1 mm to 2.36 mm), medium particles (0.5 mm to 1 mm), and fine particles (0.1 mm to 0.5 mm).

[0096] S2. Weigh 4 g of nano-talc and 6 g of nano-boehmite as the nano-modified materials. Disperse 10 g of the nano-modified materials in 0.10 L of anhydrous ethanol, then add 0.15 g of dispersant and perform ultrasonic dispersion. The power density of ultrasonic dispersion is 80 W / L, and the time is 40 min. Immediately after dispersion, take a sample to measure the zeta potential. The result is -40.5 mV, and the absolute value is greater than 35 mV, indicating that the suspension is stable.

[0097] S3. Weigh 225 g of three-graded pyrophyllite particles, including 45 g of coarse particles, 67.5 g of medium particles, and 112.5 g of fine particles (coarse, medium, and fine particle mass ratio = 2:3:5). Add the particles to a mixer, set the speed to 15 rpm, and start the tumbling process. Transfer the nano-suspension prepared in step S2 to a storage tank and spray it through an atomizing spray system. The nozzle orifice diameter is 0.8 mm, the spray pressure is 0.3 MPa, and the spraying time is approximately 3 minutes. Keep the pyrophyllite particles continuously tumbling during the spraying process. After spraying, continue tumbling for 15 minutes to allow the liquid film to fully spread. Then transfer the material to a dryer and dry it at 80℃ until the residual ethanol content is ≤0.5 wt%, obtaining a surface-coated graded powder. The resulting powder D... 50 The thickness is 0.71 mm, and the specific surface area of ​​BET is 16.8 m². 2 / g.

[0098] S4. Add 15 g of water glass binder (modulus 3.27, Baume degree 40°Bé) to the obtained graded powder by spraying evenly at a pressure of 0.2 MPa for 1 minute. Maintain the mixer speed at 20 rpm during the addition process. After the addition is complete, continue stirring for 10 minutes to obtain the mixture.

[0099] S5. Fill the mixture into a hollow cubic mold. The mold's outer cavity dimensions are 53mm × 53mm × 53mm, the mandrel dimensions are 37mm × 37mm × 37mm, and the wall thickness is 8mm. The mold material is Cr12MoV mold steel. A double-sided hydraulic press is used for pressing, with the upper and lower punches applying pressure simultaneously. The pressure is set to 280MPa, and the holding time is 20s. During pressing, the displacement of the upper and lower punches is monitored in real time, and the stroke deviation is controlled within 0.3mm. After demolding, a green cube is obtained.

[0100] S6. Place the green block into a programmable temperature-controlled oven and dry it using the following parameters in a five-stage program:

[0101] First stage: Heat to 100℃ at a rate of 1.5℃ / min, and hold at 100℃±2℃ for 8 hours;

[0102] Second stage: Increase the temperature to 130℃ at a rate of 1.0℃ / min, and hold at 130℃±2℃ for 5 hours;

[0103] The third stage: the temperature is increased to 180℃ at a rate of 0.8℃ / min, and then held at 180℃±2℃ for 3.5 hours;

[0104] Fourth stage: Increase the temperature to 230℃ at a rate of 0.5℃ / min, and hold at 230℃±2℃ for 3.5 hours;

[0105] Fifth stage: Increase the temperature to 280℃ at a rate of 0.4℃ / min, and hold at 280℃±2℃ for 4 hours.

[0106] After drying, turn off the oven power and allow the sample to cool naturally to room temperature (approximately 25°C) to obtain the finished product. The density of the finished product is measured: the overall density is 2.65 g / cm³. 3 The density difference between the upper and lower surfaces is 0.04 g / cm³. 3 .

[0107] Comparative Example 1

[0108] The only difference from Example 1 is the omission of the preparation of the nano-suspension and the spraying steps. Specifically, step S2 is omitted; 10g of the nano-modified material is directly added in dry powder form to 225g of three-graded pyrophyllite particles (coarse:medium:fine = 2:3:5), and mechanically mixed in a mixer at 20 rpm for 20 minutes. After mixing, the bonding and granulation process (15g of water glass) in step S4 is performed directly. All other methods and steps are exactly the same as in Example 1.

[0109] The overall density of the finished product was measured to be 2.60 g / cm³. 3 The density difference between the upper and lower surfaces is 0.07 g / cm³. 3 .

[0110] Comparative Example 2

[0111] The only difference from Example 1 is that it does not include the nano-modified materials. Specifically, all operations in step S3 are omitted, and the 225g of tertiary-graded pyrophyllite particles (coarse:medium:fine = 2:3:5) are directly subjected to the bonding and granulation process of step S4. The amount of water glass binder is adjusted to 25g (keeping the total material amount at 250g). The remaining steps are exactly the same as in Example 1.

[0112] The overall density of the finished product was measured to be 2.54 g / cm³. 3 The density difference between the upper and lower surfaces is 0.08 g / cm³. 3 .

[0113] Comparative Example 3

[0114] The only difference from Example 1 is that the forming method is single-sided pressing. Specifically, step S5 uses a single-sided top-pressing process, with only the upper punch applying pressure of 280 MPa, while the lower punch remains stationary as a support platform, and the pressure holding time is 20 seconds. There is no stroke deviation control between the upper and lower punches. The remaining steps are exactly the same as in Example 1.

[0115] The overall density of the finished product was measured to be 2.60 g / cm³. 3 The density difference between the upper and lower surfaces is 0.14 g / cm³. 3 .

[0116] Comparative Example 4

[0117] The only difference from Example 1 is the use of a conventional three-stage drying process. Specifically, the drying process in step S6 is as follows: the first stage involves heating to 80°C at a rate of 2°C / min and holding for 4 hours; the second stage involves heating to 150°C at a rate of 2°C / min and holding for 4 hours; and the third stage involves heating to 250°C at a rate of 2°C / min and holding for 4 hours. The weight loss ratio is not monitored in any stage. The remaining steps are exactly the same as in Example 1.

[0118] During the drying process, it was observed that: at the end of the first stage, a small number of samples showed fine cracks on their surfaces; at the end of the second stage, about 5% of the samples showed obvious cracks; and at the end of the third stage, about 10% of the samples showed through cracks.

[0119] The overall density of the finished product was measured to be 2.59 g / cm³. 3 The density difference between the upper and lower surfaces is 0.06 g / cm³. 3 .

[0120] Application examples

[0121] Parallel experiments were conducted according to the raw material ratios and preparation methods of Examples 1-3 and Comparative Examples 1-4. For each example and comparative example, 40 sealed pressure-transmitting medium samples were prepared, and their crack resistance and sealing performance were tested. The arithmetic mean was taken, and the test results are shown in Table 2. Among them, only samples with intact appearance were selected for testing in Comparative Example 4.

[0122] Table 2

[0123] Cracking rate during sintering at 800℃ (%) Seal leakage volumetric flow rate (mL / min) at 0.5 MPa Example 1 0 0.08 Example 2 0 0.11 Example 3 0 0.13 Comparative Example 1 10 0.35 Comparative Example 2 25 0.48 Comparative Example 3 40 0.41 Comparative Example 4 50 0.52

[0124] Results and Discussion:

[0125] The overall density of Examples 1 to 3 all reached 2.65 g / cm³. 3 The density difference between the upper and lower surfaces does not exceed 0.04 g / cm³. 3 All samples from each embodiment showed no cracking, and the leakage volumetric flow rate at 0.5 MPa was below 0.13 mL / min, demonstrating superior performance compared to all comparative examples. This indicates that the present invention can simultaneously achieve the comprehensive goals of high density, low density difference, crack resistance, and excellent sealing performance.

[0126] Comparative Example 1, using only dry mixing, failed to achieve uniform coating of the nano-modified material on the surface of the pyrophyllite particles, increasing the cracking rate and sealing leakage volumetric flow rate. Comparative Example 2, without any nano-modified material, showed severe deterioration in all performance aspects, with a cracking rate reaching 25% and a sealing leakage volumetric flow rate as high as 0.48 mL / min. Comparative Example 3, employing a single-sided pressing technique, resulted in a density difference between the upper and lower surfaces increasing from 0.02 g / cm³. 3 It rose sharply to 0.14 g / cm³ 3 The cracking rate increased from 0% to 40%, and the sealing leakage volume flow rate reached 0.41 mL / min. Although the density difference of the sample obtained by the conventional three-stage drying method used in Comparative Example 4 was the lowest among the comparative examples, the cracking rate and sealing leakage volume flow rate were much higher than the experimental data of the examples and other comparative examples.

[0127] The experimental results above demonstrate that the technical solution of this invention, through a complete process chain including three-stage particle size distribution, ultrasonic dispersion and spray coating of nano-suspension, double-sided synchronous pressing, and five-stage drying, achieves synergistic cooperation between each step, resulting in unexpected technical effects that cannot be achieved by a single step or simple combination. This invention provides a high-performance, stable, safe, and reliable pressure-transmitting and sealing solution for the high-temperature and high-pressure synthesis of synthetic diamond.

[0128] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing a high-density, crack-resistant, nano-modified pyrophyllite composite sealing and pressure-transmitting medium, characterized in that, The raw materials for preparing the pressure transmission medium, by weight, include the following components: 88-94 parts of natural pyrophyllite, 2-6 parts of nano-modified material, and 4-8 parts of water glass binder, and the total weight of each component is 100 parts. The nano-modified material is at least one of nano-talc, nano-diatomite, nano-rutile, and nano-hematite; The specific preparation method includes the following steps: (1) Crush, grind and screen the natural pyrophyllite ore to separate coarse particles with a particle size of 1 mm to 2.36 mm, medium particles with a particle size of 0.5 mm to 1 mm and fine particles with a particle size of 0.1 mm to 0.5 mm. Weigh the pyrophyllite particles in each particle size range according to the mass ratio of coarse, medium and fine particles of (2 to 3): 3: (4 to 5) and mix them evenly. (2) The nano-modified material is dispersed in anhydrous ethanol, and a dispersant is added for ultrasonic dispersion to form a stable nano suspension; (3) The suspension obtained in step (2) is applied to the surface of the pyrophyllite particles in a rolling state by atomized spraying, mixed evenly and evaporated to dry, to obtain a graded powder with surface coating. (4) Add water glass binder to the graded powder obtained in step (3), stir evenly, and obtain a mixture; (5) Place the mixture obtained in step (4) into a mold and press it into shape using a double-sided pressing process to obtain a green block; (6) Place the green block obtained in step (5) into a programmable temperature-controlled oven for five-stage stepped heating and drying, and the finished product is obtained after cooling.

2. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, The particle size D of the nanotalc 50 The particle size D of nano-diatomite ranges from 50 nm to 200 nm. 50 The particle size D of nano-rutile is 30 nm to 150 nm. 50 The particle size D of nano-hematite ranges from 40 nm to 120 nm. 50 The wavelength range is 40 nm to 120 nm.

3. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (2), the mass ratio of the nano-modified material to anhydrous ethanol is 1:(5.7~19.5). The dispersant is polyethylene glycol 400 or polyvinylpyrrolidone K30, and the amount of the dispersant added is 0.5% to 3% of the weight of the nano-modified material. The solid content of the nano-suspension is 5 wt%~15 wt%, and the absolute value of the Zeta potential is ≥35 mV.

4. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (3), the nozzle orifice diameter of the atomizing spray is 0.5 mm to 1.5 mm, the spray pressure is 0.2 MPa to 0.5 MPa, and the spray flow rate is 50 mL / min to 200 mL / min.

5. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (3), the D of the surface-coated graded powder 50 Its thickness ranges from 0.3 mm to 1.5 mm, and its specific surface area is 10 m². 2 / g~30 m 2 / g.

6. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (4), the modulus of the water glass adhesive is 2.0~3.5 and the Baume degree is 30°Bé~50°Bé.

7. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (5), the pressing pressure of the double-sided top pressing process is 250 MPa~300 MPa, and the holding time is 10 s~30 s.

8. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (6), the temperature, holding time, and heating rate of each stage of the five-stage program drying meet the following conditions: First stage: Increase the temperature to 95℃~105℃ at a rate of 1.0℃ / min~2.0℃ / min, and hold for 6 h~10 h; Second stage: Increase the temperature to 115℃~135℃ at a rate of 0.5℃ / min~1.5℃ / min, and hold for 4 h~6 h; The third stage: the temperature is increased to 175℃~185℃ at a rate of 0.5℃ / min~1.0℃ / min, and held for 3 h~4 h; Fourth stage: Increase the temperature to 225℃~235℃ at a rate of 0.3℃ / min~0.8℃ / min, and hold for 3 h~4 h; Fifth stage: Increase the temperature to 275℃~285℃ at a rate of 0.3℃ / min~0.5℃ / min, and hold for 3 h~5 h.

9. The nano-modified pyrophyllite composite sealing pressure transmission medium as described in claim 1, characterized in that, In step (6), the bulk density of the pressure transmitting medium is 2.65 g / cm³. 3 The density difference between its upper and lower surfaces is 0.04 g / cm³. 3 The following products showed no cracking after high-temperature sintering, and the volumetric flow rate of the leaking seal was below 0.13 mL / min.

10. The nano-modified pyrophyllite composite sealing pressure transmission medium prepared by the method according to any one of claims 1-9.